الاحتياجات المعرفية للأخصائيين العاملين بالمدارس المطبقة لنظام الدمج - إبراهيم، داليا عبدالمولي عبدالنبي Ibrahim, Dalia Abdulmawla Abdulnabi (جامعة الفيوم - كلية الخدمة الاجتماعية, 2021)
لقد أصبح دمج الأطفال ذوي الإعاقة البسيطة في التعليم والمجتمع أمرا ضروريا لاعتبارات كثيرة منها ما يتعلق بالأطفال ذوي الإعاقة أنفسهم وضرورة معاملتهم معاملة انسيابية تقتضي إدماجهم مع أقرانهم من الأسوياء، كما أن لنظام الدمج أهمية كبيرة حيث يعد لنظام الدمج في تربية وتعليم الأطفال ذوي الإعاقة أكثر اتساقا مع الحقوق الإنسانية من نظام التربية الخاصة حيث يشعر التلميذ ذوي الإعاقة بالثقة في النفس ويشعره بقيمته في الحياة ويتقبل إعاقته ويدرك قدراته وإمكانياته في وقت مبكر ويشعر بانتمائه إلى أفراد المجتمع الذي يعيش فيه، وبالرغم من مساعدة هؤلاء الأطفال ذوي الإعاقة على التأقلم في المجتمع من خلال دمجهم في المدرسة، إلا أن هناك تحديات تواجه نجاح عملية الدمج منها أن الكادر البشرى الذي يعمل مع هذه الفئة غير ملم بآليات العمل مع الأطفال ذوي الإعاقة، فعدم إلمام الكادر البشرى بموضوع الدمج أو عدم حصوله على التدريب المناسب لكل ينتج عنه مردود سيئ يؤثر على نجاح البرنامج الذي يتطلب إعداد المعلمين والأخصائيين الاجتماعيين في مرحلة ما قبل الدمج والتدريب والتأهيل أثناء الدمج للعاملين في المشروع، وباعتبار أن الأخصائي الاجتماعي أحد عناصر العمل الفريقي بمدارس الدمج فإنه يحتاج إلي عملية تحسين وتطوير مستمر لأداءه المهني حتي يكون على قدر من الكفاءة في أداء عمله المهني، لذا يجب على الأخصائيين الاجتماعيين العاملين بمدارس الدمج أن يكونوا حريصين على الاستزادة المعرفية من خلال التدريب المستمر كما يجب على المدارس التي يعملون بها أن تزودهم بكل جديد سواء عن طريق النشرات الدورية أو اللقاءات العلمية وأن توفر لهم برامج تدريب مستمرة ومتدرجة ضمانا للارتفاع الإيجابي في أدائهم المهني وليكونوا أكثر قدرة على أداء مسئولياتهم المهنية، وقد سعت هذه الدراسة الوصول إلي أهم الاحتياجات المعرفية للأخصائيين الاجتماعيين العاملين بالمدارس المطبقة لنظام الدمج.
The inclusion of children with mild disabilities in education and society has become necessary for many considerations, including those related to children with disabilities themselves, and the need to treat them smoothly, requiring their inclusion with their peers, and the integration system is of great importance, as the inclusion system in the education and education of children with disabilities is more consistent. With human rights from the special education system, where the student with disabilities feels self-confidence, makes him feel his value in life, accepts his disability, realizes his abilities and potentials at an early age and feels belonging to the members of the community in which he lives, despite helping these children with disabilities to adapt in society by integrating them In the school, however, there are challenges facing the success of the integration process, including that the human cadre working with this group is not familiar with the mechanisms of working with children with disabilities. The lack of knowledge of the human cadre in the issue of integration or the lack of appropriate training for each category results in a bad outcome that affects the success of the integration process. The program that requires the preparation of teachers and social workers in the pre-integration stage and training and rehabilitation during the integration of project workers, and considering that the specialist The social worker is one of the elements of team work in the integration schools. It needs a process of continuous improvement and development of its professional performance in order to be efficient in the performance of its professional work. Therefore, social workers working in the integration schools must be keen on increasing knowledge through continuous training, and the schools that They work with it to provide them with everything new, whether through periodic bulletins or scientific meetings, and to provide them with continuous and gradual training programs to ensure a positive improvement in their professional performance and to be more able to perform their professional responsibilities. This study sought to reach the most important knowledge needs of social workers working in schools applying the system merging.
Keywords: الأطفال المعاقيين -- الحقوق الإنسانية -- الأخصائي الاجتماعي